Komunikasi dalam Manajemen Reputasi Korporasi - André A. Hardjana (FISIP Universitas Atma Jaya Yogyakarta, 2008)
Abstract: Reputation is an important concept for the corporation. In the highly competitive situation, reputasi help the corporation to develop and maintain its existency. For this reason, reputation has to be managed by creating appropriately strategic communication. Reputation is different from corporate identity and corporate image. Corporate reputation is more established, stable and testable than the corporate identity and corporate image. However, to build corporate reputation, we need to manage corporate image and corporate identity by applying a strategic corporate communication.